Determinants of Male Infertility among Married Couples in a Tertiary Hospital in Bangladesh (Medicine Today, 2022)
Introduction: Infertility may be defined as a lack of conception after 1 – 2 years of unprotected coitus. In a normal population approximately 60 % of couples will achieve pregnancy within 6 months, 80 % by 12 months, and 90 % by 18 months leaving approximately 10 % of couples arbitrarily classified as infertile. A general classification of causes of infertility are male 35 – 40 %, female 40 – 50 %, sexual 10 % and unknown 10 %.Objective: To see the determinants of male infertility among the infertile couples who attending the outpatient department of infertility unit of the department of obstetrics and gynaecology of Bangabandhu Shiekh Mujib Medical University, Shahbag, Dhaka.Materials and Methods: This prospective observational study was conducted in the Infertility unit, Department of Obstetrics and Gynaecology, Bangabandhu Shiekh Mujib Medical University (BSMMU), Dhaka, during the period from 31.10.2016 to 21.03.2018. 500 infertile male patients were recruited from the out-patient department of infertility unit who came to take treatment for their infertility problem. They were analyzed by data collection sheet and the results were plotted in the table.Result: The socio-demographic characteristics of the study subjects (n = 500).Husbands age group was 22 -55in years, Mean ± SD (34.0 ± 5.9). Educational level of male partners was, no education = 5 (1.0%), primary = 27 (5.4%), secondary = 152 (30.4%), graduate = 148 (29.6%), postgraduate = 74 (14.8%), 0thers = 94 (18.8%). Occupation of male partners was, unemployed = 6 (1.2%), service = 356 (71.2%), business = 138 (27.6%). Diabetes: In male = 28 (5.6%).Mumps: In male = 7 (1.4%). Chicken pox: In male = 18 (3.6%). Hypertension: In male = 10 (2.0%). Orchitis: In male = 6 (1.2%). Personal history of husband: Smoking = 129 (25.8%). In male patients, Testosterone level normal (10 – 30 nmol/L) in 133 (26.6%) patients and above normal (>30 nmol/L) in 367 (73.4%) patients. The semen analysis of the husbands of the infertile female patients.In quality of semen poor (